Matematyka

Autorzy:Wojciech Babiański, Lech Chańko, Joanna Czarnowska

Wydawnictwo:Nowa Era

Rok wydania:2015

Uprość wyrażenie 4.57 gwiazdek na podstawie 7 opinii
  1. Liceum
  2. 1 Klasa
  3. Matematyka

`a)`

`(x+3)^2-(x-4)^2+2x=`

`=(x^2+2*x*3+3^2)-(x^2-2*4*x+4^2)+2x=`

`=x^2+6x+9-x^2+8x-16+2x=`

`=16x-7`

 

Obliczamy wartość liczbową wyrażenia: 

`16x-7=16sqrt5-7`

 

 

 

`b)`

`(x-sqrt2)^2-(x+sqrt2)^2+sqrt18x=`

`=x^2-2*x*sqrt2+sqrt2^2-(x^2+2*x*sqrt2+sqrt2^2)+sqrt18x=`

`=x^2-2sqrt2x+2-x^2-2sqrt2x-2+sqrt9*sqrt2x=`

`=-4sqrt2x+3sqrt2x=-sqrt2x`

 

Obliczamy wartość liczbową wyrażenia: 

`-sqrt2x=-sqrt2*sqrt6/2=-(sqrt(2*6))/2=-sqrt12/2=-(sqrt4*sqrt3)/3=-(2sqrt3)/2=-sqrt3`

 

 

`c)`

`(3x-sqrt3)^2+(4x+sqrt3)^2-(5x-sqrt3)^2=`

`=((3x)^2-2*3x*sqrt3+sqrt3^2)+((4x)^2+2*4x*sqrt3+sqrt3^2)-((5x)^2-2*5x*sqrt3+sqrt3^2)=`

`=9x^2-6sqrt3x+3+16x^2+8sqrt3x+3-25x^2+10sqrt3x-3=`

`=12sqrt3x+3`

 

Obliczamy wartość liczbową wyrażenia:

`12sqrt3x+3=strike12^3sqrt3*((-sqrt3)/strike4^1)+3=-9+3=-6`